A Feasibility Study of Photoacoustic Detection of Hidden Dental Caries Using a Fiber-Based Imaging System - Takuya Koyama; Satoko Kakino; Yuji Matsuura (Applied Sciences, 2018)
In this paper, the feasibility of an optical fiber-based photoacoustic imaging system for detecting caries lesions inside a tooth is examined. Models of hidden caries were prepared using a pigment with an absorption spectrum similar to that of real caries lesions, and the occlusal surface of the model teeth containing the pigment was irradiated with laser pulses with a wavelength of 532 nm. An examination of the frequency spectra of the emitted photoacoustic waves revealed that the spectra from simulated caries lesions included frequency components in the range of 0.5–1.2 MHz that were not seen in the spectra from healthy parts of the teeth. This indicates that hidden caries can be detected via a photoacoustic imaging technique. Accordingly, an imaging system for clinical applications was fabricated. It consists of a bundle of hollow-optical fibers for laser radiation and an acoustic probe that is attached to the tooth surface. Results of ex vivo imaging experiments using model teeth and an extracted tooth with hidden caries lesions show that relatively large caries lesions inside teeth that are not seen in visual inspections can be detected by focusing on the above frequency components of the photoacoustic waves.